Issues Pertaining to Malaysian Halal Food : Halalan Tayyiban as a Guideline - Sazelin , Arif (2009)

(untitled)
Consumption of food is not just to satisfy physical needs but also has spiritual significance. There was a time when people only consumed fresh and natural food. But with the advent of food technology, we have been eating more processed food containing chemicals, additives and preservatives to match with demands and perfections in food production. Islam is a religion concerned with every aspect of the life of an individual Muslim. In Islam, the consumption of halal food is obligatory in serving Allah, the Creator and the AlMighty. Allah is guiding us in His Holy Quran to eat what is permissible/lawful (halal) and good (tayyib) food from the Earth. Nowadays, different types as well variety of food offered in the market often confuse the Muslim consumers and most of them unaware of what they have consumed. Doubtful about the good quality (halal and tayyib) of food appear in every aspects ‘from farm to fork’ beginning from the ingredients, processing, handling and packaging. Simultaneously, this scenario has become increasingly challenging for Muslim consumers to determine whether the food they consume are religiously acceptable (halal) or not. Not only that, the abusing of halal logo and the questionable halal status of food also contribute to the halal haram issues of food. Hence, this paper will focus on some fraudulent issues pertaining to halal food industry in Malaysia with some suggestion on how to tackle them effectively with the implementation of halalan tayyiban. The concept of halalan tayyiban (lawful and good) which encompass health, hygiene, sanitation, safety and quality is adopted in globally recognized Malaysian Halal Standard MS 1500:2004 - Production, Preparation, Handling and Storage. It is the question on how does the wholesomeness of halalan tayyiban really applied throughout the food process. Undoubtedly, food that we eat and consume is only halal if the raw materials and ingredients used are halal and it is fully compatible to the Islamic guidelines. Thus, the high quality and safety aspects underlined by the standards of halal and tayyib should be highlighted to offer reassurance to those of the Muslim faith and to preserve the wholesomeness of halal food in the market.